Empowering Leadership In Employee Career Establishment (Case Study in East Java Banking) - Evi Yulia; Nurus Safa’atillah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The purpose of this study is to determine the relationship between empowering leadership and career success and the mediating role of psychological empowerment in the process of forming employee careers. The research method used is a quantitative research type with a survey method. The population of banking employees with a research sample of 300 banking employees in East Java. Analysis using PLS SEM. The results of the study show that empowering leadership is positively related to psychological empowerment and career success. besides that psychological empowerment also plays a positive role in mediating the relationship between empowering leadership and career success. This study outlines that psychological empowerment is an effective stimulus in enhancing the relationship between empowering leadership and career success. implications of contributing practically in the development of theories and strategies that can be applied in banking. Additionally future research directions are suggested.